Need assessment of Al-Mumtaaz Islamic Elementary School students’ food literacy competencies - Haura Dzakira Sahla; Dadang Sukirman (Himpunan Pengembang Kurikulum Indonesia, 2024)
Al-Mumtaaz Islamic Elementary School Karawang has created various programs to support students' food literacy knowledge and skills. However, the programs implemented by schools have not been supported with systematic curriculum planning and clear food literacy competencies that meet students’ needs. Therefore, this research aims to develop food literacy competency and identify the student's actual performance in food literacy. This research uses McNeil's Need Assessment Model method, which consists of 4 stages. The first stage produces several learning objectives with insight into food literacy from various literature sources. The second stage produces food literacy competencies for elementary school students, which multiple experts have validated. The third stage is an initial formative assessment to look for gaps between food literacy competencies and the conditions of 58 Phase A (Level 1 & 2) students. The initial formative assessment results show that 98,3% of students are above the minimum competency category. Even so, there is still a gap in food literacy knowledge among students. The final stage is to provide program recommendations for schools according to the analysis of student performance. Abstrak SD Islam Al-mumtaaz Karawang telah membuat beragam program untuk mendukung pengetahuan dan keterampilan siswa sekolah dasar untuk memperoleh kecakapan literasi pangan. Namun, program yang telah dilakukan oleh sekolah belum ditunjang dengan perencanaan kurikulum yang baik dan tujuan kompetensi literasi pangan yang jelas dan sesuai kebutuhan usia peserta didik, latar belakang budaya, latar belakang agama, dan lingkungan sekolah. Oleh sebab itu, penelitian ini bertujuan untuk menyusun tujuan kompetensi literasi pangan dan mengidentifikasi kemampuan aktual siswa berdasarkan tujuan kompetensi yang telah disusun. Penelitian ini menggunakan metode Need Assessment Model dari McNeil yang terdiri dari 4 tahapan. Tahap pertama menghasilkan sejumlah tujuan - tujuan pembelajaran yang memiliki wawasan literasi pangan dari berbagai sumber literatur. Tahap kedua menghasilkan peta kompetensi literasi pangan untuk jenjang SD yang telah divalidasi oleh berbagai ahli. Tahap ketiga adalah melakukan asesmen formatif awal untuk mencari kesenjangan antara kompetensi literasi pangan dengan kondisi aktual siswa SD Fase A sejumlah 58 siswa. Dimana hasil asesmen formatif awal menunjukkan bahwa 98,3% murid SD Fase A menunjukkan tingkat kompetensi literasi pangan pada kategori cakap dan mahir. Meskipun begitu, masih terdapat kesenjangan pengetahuan literasi pangan pada siswa. Tahap terakhir adalah memberikan program rekomendasi untuk sekolah sesua dengan analisis kemampuan siswa. Kata Kunci: pengembangan kurikulum; literasi pangan; asesmen kebutuhan